2011
DOI: 10.1117/12.872945
|View full text |Cite
|
Sign up to set email alerts
|

Generation of UV and blue light by using off-axis pumping for fluorescence lifetime spectroscopy

Abstract: We report on generation of blue light exploiting high-order mode propagation in a microstructured fiber pumped by a Ti:Sapphire close to the zero-dispersion wavelength of the first high-order mode. An new interesting regime was observed with axial offset pump. With 230 mW of incident pump power we generated over 3 mW in the 450-510 nm window achieving 50 μW/nm power density. In a final round of measurements we were able to show generation of a peak at 350 nm. This complex regime has still to be fully investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Further work will also need to better investigate the optimum interplay of pump wavelength and ZDW wavelength. As previously reported by changing the power level at a fixed wavelength we were able to tune the spectral peaks [12]. However in this case we had enough power to perform measurement by simply slicing the supercontinnum spectrum at a fixed pump power and pump wavelength.…”
Section: Pumping Scheme and Uv-visible Generationmentioning
confidence: 89%
See 3 more Smart Citations
“…Further work will also need to better investigate the optimum interplay of pump wavelength and ZDW wavelength. As previously reported by changing the power level at a fixed wavelength we were able to tune the spectral peaks [12]. However in this case we had enough power to perform measurement by simply slicing the supercontinnum spectrum at a fixed pump power and pump wavelength.…”
Section: Pumping Scheme and Uv-visible Generationmentioning
confidence: 89%
“…[12]. The use of a custom made MSF [12,13] allowed us to achieve a regime quite different from the one reported in [8][9][10]. We found that using off-axis pumping and being able to carefully tune the pump wavelength close to first order mode ZDW we can very efficiently generate UV and visible light.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…We also demonstrated the similar peaks in the output spectra were formed in the IR up to 2.5 μm. [12] In this work we investigate the characteristic of this regime as we tune the pump power and the excitation wavelength approaching around the zero-dispersion wavelength of the first-order mode. We aimed to generate light in the visible range (300 nm -600 nm wavelength interval) for an application to confocal fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 99%